Vessel-encoded dynamic magnetic resonance angiography using arterial spin labeling. - Okell, T; Chappell, M; Woolrich, M; Günther, M; Feinberg, D; Jezzard, P (2010)
A new noninvasive MRI method for vessel-selective angiography is presented. The technique combines vessel-encoded pseudocontinuous arterial spin labeling with a two-dimensional dynamic angiographic readout and was used to image the cerebral arteries in healthy volunteers. Time-of-flight angiograms were also acquired prior to vessel-selective dynamic angiography acquisitions in axial, coronal, and/or sagittal planes, using a 3-T MRI scanner. The latter consisted of a vessel-encoded pseudocontinuous arterial spin labeling pulse train of 300 or 1000 ms followed by a two-dimensional thick-slab flow-compensated fast low-angle shot readout combined with a segmented Look-Locker sampling strategy (temporal resolution = 55 ms). Selective labeling was performed at the level of the neck to generate individual angiograms for both right and left internal carotid and vertebral arteries. Individual vessel angiograms were reconstructed using a bayesian inference method. The vessel-selective dynamic angiograms obtained were consistent with the time-of-flight images, and the longer of the two vessel-encoded pseudocontinuous arterial spin labeling pulse train durations tested (1000 ms) was found to give better distal vessel visibility. This technique provides highly selective angiograms quickly and noninvasively that could potentially be used in place of intra-arterial x-ray angiography for larger vessels.